The Piver’s Island Coastal Observatory – a decade of weekly+ observations reveal the press and pulse of a changing temperate coastal marine system - Johnson, Zackary I.; Hunt, Dana E., the PICO Consortium; Wang, Guangyi; Blinebry, Sara; Xie, Ningdong; Wheeler, Jay; Ward, Christopher S.; Yung, Cheuk-Man; Gu, Junyao; Juarez, Doris L.; Yingbo, Duan; et al. (Frontiers in Marine Science, 2025)
Historically, oceanographic time-series have focused on long-term measurements of large open ocean gyres; yet, the coastal oceans, with their high productivity, tidal impacts, human feedbacks, and land-sea coupling, represent critical regions for predicting ocean dynamics and biogeochemistry under global change. The Piver’s Island Coastal Observatory (PICO) time-series, located in the second largest estuarine system on the US East Coast (Albemarle-Pamlico Sound), comprises more than a decade of weekly (or more frequent) measurements of core physical, chemical, and biological oceanographic variables. PICO provides insight into a coastal, mesotrophic ecosystem in an ecologically-diverse and biochemically-active region impacted by global change. Here, we report on a decade of observations focusing on pulse and press ecosystem changes. We observe strong mean annual cycles in environmental variables including temperature (10.1-28.9°C), pH (7.89-8.12), dissolved inorganic carbon (DIC: 1965 – 2088 µM), chlorophyll (2.54-5.77 mg Chl m-3), upon which are layered episodic disturbances (e.g., tropical cyclones) that dramatically and persistently (>1 month) impact this ecosystem. Among other variables, long term trends in pH (-0.004 ± 0.001 y-1; p<0.01), DIC (-9.8 ± 1.5 µM y -1; p<0.01) and chlorophyll (-0.17 ± 0.02 µg L-1 y-1; p<0.01) are exceeding those observed in the open ocean, suggesting an ecosystem in flux. These analyses provide a benchmark for future studies of the impact of changing climate and oceanographic climatology; further research will use this long-term research to developed targeted sampling and experimental manipulations to better understand ecosystem structure and function.